2021
DOI: 10.1097/cce.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Multimodal Physiologic Approach to Mechanical Ventilation in Patients With Obesity and Severe Acute Respiratory Distress Syndrome Reduced Venovenous Extracorporeal Membrane Oxygenation Utilization

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The LRT group had the least lung overdistention and collapse, better compliance, and better oxygenation. Retrospectively, the LRT approach was safe, efficient, and effective at guiding ICU management [24 ▪ ], yielded higher PEEP for patients with BMI ≥ 35 kg/m 2 without causing hemodynamic instability or overdistention [25 ▪ ], was associated with improved survival in patients with a BMI ≥ 40 kg/m 2 (31% vs. 16% mortality at 28 days and 41% vs. 22% at 1 year) [26 ▪ ], and was associated with reduced need for ECMO in patients with a BMI ≥ 30 kg/m 2 [27 ▪ ]. This compelling data supports the benefit, even on mortality, of individualizing ventilatory management, and the role of EIT in this pursuit.…”
Section: Lung Rescue Team and Obesitymentioning
confidence: 99%
“…The LRT group had the least lung overdistention and collapse, better compliance, and better oxygenation. Retrospectively, the LRT approach was safe, efficient, and effective at guiding ICU management [24 ▪ ], yielded higher PEEP for patients with BMI ≥ 35 kg/m 2 without causing hemodynamic instability or overdistention [25 ▪ ], was associated with improved survival in patients with a BMI ≥ 40 kg/m 2 (31% vs. 16% mortality at 28 days and 41% vs. 22% at 1 year) [26 ▪ ], and was associated with reduced need for ECMO in patients with a BMI ≥ 30 kg/m 2 [27 ▪ ]. This compelling data supports the benefit, even on mortality, of individualizing ventilatory management, and the role of EIT in this pursuit.…”
Section: Lung Rescue Team and Obesitymentioning
confidence: 99%
“…The benefits reported from the use of this position in "classic" acute respiratory distress syndrome (ARDS) were also confirmed in COVID-19 associated ARDS 2 . This strategy, requiring highly trained personnel and not devoid of possible complications [3][4][5] , has thus been included in the guidelines for the treatment of moderate and severe COVID-19 associated ARDS 6 . Indeed, while results from randomized controlled trials in this specific population are lacking, placing subjects with COVID-19 associated ARDS in PP decreases alveolar collapse, hyperinflation, and improves the homogeneity of lung aeration and ventilation 2,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In a previously published work performed at Massachusetts General Hospital in a similar population ( 5 ), our research team demonstrated that patients with obesity are characterized by a baseline elevation in pleural pressure that necessitates a higher than normally used PEEP to allow end-expiratory positive transpulmonary pressure. Moreover, 77% (10 of 13) of patients with ARDS with obesity who apparently failed conventional ventilator management and were deemed suitable candidates for ECMO responded to individualized PEEP titration maneuvers, and no longer required extracorporeal support.…”
mentioning
confidence: 99%